DEVELOPMENT OF A DIFFERENTIATED LEARNING MEDIA MODEL BASED ON MICRO LEARNING IN MATHEMATICS SUBJECTS IN THE STUDY OF NUMBERS IN PRIMARY SCHOOLS - Sandi Budi Iriawan; Dina Mayadiana; Andhin Dyas Fitriani; Rosiana Mufliva; sendi fauzi giwangsa (Jurnal Cakrawala Pendas, 2024)
Mathematics learning media for elementary school level currently generally does not facilitate student diversity from various aspects of diversity, both content, process, product, and student learning environment by considering students' readiness, interests and learning profile to master certain competencies. Learning media is packaged monotonously without involving ICT, causing boredom for students, especially at the elementary school level, who are generally unable to endure long periods of learning using learning media that are not varied. Such mathematics learning media is not yet relevant to the principles of the current curriculum, namely the Kurikulum Merdeka which has a growth mindset. In the Kurikulum Merdeka, teachers are expected to be proactive figures (proactive teachers) who have a growth mindset by viewing that each student is unique and different, so it is necessary to provide services that accommodate students' various learning needs or differentiated learning based on the results of the initial assessment. Learning media also ideally strengthens quality learning experiences, including being developed and packaged digitally according to students' current learning needs with a micro learning approach so as not to bore students, containing various elements (text, audio, video, animation and infographics), containing only basic or important material, allows students to use it for a relatively short period of time, and allows students to use it anytime and anywhere. The research that has been carried out aims to develop a differentiated learning media model based on micro learning in Mathematics subjects in the field of Number studies in elementary school.